2013
DOI: 10.1002/jrs.4236
|View full text |Cite
|
Sign up to set email alerts
|

SERS investigation on the adsorption and photoreaction of 4‐nitroanisole in Ag hydrosols

Abstract: The adsorption of 4‐nitroanisole on silver colloidal nanoparticles was investigated by surface‐enhanced Raman spectroscopy (SERS). Actually, the chemical binding with a metal substrate may play a role in changing the electronic structure of this molecule, which can be considered a push–pull chromophore, because an internal charge‐transfer occurs between methoxy and nitrogroup. A SERS signal could be detected only in chloride‐activated silver colloids, but the spectrum recorded with green‐light excitation was n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 48 publications
(72 reference statements)
2
23
0
Order By: Relevance
“…It was concluded that the chemical binding with a metal substrate may play a role in changing the electronic structure of this molecule, which can be considered a push-pull chromophore, because of an internal charge-transfer that occurs between its methoxy and nitro groups. [51] Muntean and coworkers reported the SERS spectra of seven genomic DNAs from leaves of chrysanthemum. They conclude that the results of this study will generate information that is valuable for the development of label-free DNA detection for chemical probing in living cells.…”
Section: Sers Substratesmentioning
confidence: 99%
See 1 more Smart Citation
“…It was concluded that the chemical binding with a metal substrate may play a role in changing the electronic structure of this molecule, which can be considered a push-pull chromophore, because of an internal charge-transfer that occurs between its methoxy and nitro groups. [51] Muntean and coworkers reported the SERS spectra of seven genomic DNAs from leaves of chrysanthemum. They conclude that the results of this study will generate information that is valuable for the development of label-free DNA detection for chemical probing in living cells.…”
Section: Sers Substratesmentioning
confidence: 99%
“…Muniz‐Miranda investigated the adsorption of 4‐nitroanisole on silver colloidal NPs SERS. It was concluded that the chemical binding with a metal substrate may play a role in changing the electronic structure of this molecule, which can be considered a push‐pull chromophore, because of an internal charge‐transfer that occurs between its methoxy and nitro groups . Muntean and coworkers reported the SERS spectra of seven genomic DNAs from leaves of chrysanthemum.…”
Section: Introductionmentioning
confidence: 99%
“…As reported in a contribution to the conference on the SERS investigation of 4‐anisole, a typical push–pull molecule with an electron‐drawing and electron‐donor group, the surface effect may appear even more complicated. When illuminated by the laser green line and in the presence of chloride ion, in fact, the surface promotes the photoreduction of the nitro‐group to azoderivative as proved by the appearance of –N = N– stretching frequency in the surface enhanced Raman spectrum . The peculiarity of SERS as a chemical analytical methodology has motivated its application to the detection and characterization of molecules present at bioactive concentrations such as drugs.…”
Section: Surface‐enhanced Raman Spectroscopymentioning
confidence: 99%
“…When illuminated by the laser green line and in the presence of chloride ion, in fact, the surface promotes the photoreduction of the nitro-group to azoderivative as proved by the appearance of -N = N-stretching frequency in the surface enhanced Raman spectrum. [6] The peculiarity of SERS as a chemical analytical methodology has motivated its application to the detection and characterization of molecules present at bioactive concentrations such as drugs. The discovery of sport doping drugs in urine is a topical analytical subject nowadays.…”
Section: Solid State and Materials Sciencementioning
confidence: 99%
“…Currently the SERS method is used for both the study of surface itself [1][2][3][4] and the investigation of the adsorbed molecules [5][6][7][8][9]. In terms of adsorption chemistry SERS is particularly valuable because there are no alternative locally sensitive methods for the investigation the state of the adsorbate.…”
Section: Introductionmentioning
confidence: 99%